Perencanaan Strategis Dalam Meningkatkan Kinerja Organisasi - Juwita Nur Aisyah; M Alfi Aulia; Qurotul Ayuni; Mualimin Mualimin (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Strategic Planning in organizations is the structured process of setting long-term goals and choosing the best strategies to achieve them, with the aim of improving organizational performance. Strategic planning is important because it covers various aspects in the long term, provides a basic framework for the organization's activities, and allows the achievement of desired performance.. The purpose of this study describes the role of strategic planning in improving organizational performance by using literature studies as a method of collecting data with libraries, reading and recording and processing research materials. Data collection techniques involve gathering information from written or printed sources, such as books, journals, articles, reports, and other documents. The results of this study concluded that strategic planning is identified as a comprehensive long-term plan, strategic planning is not just a static document, but an active guide in carrying out activities in accordance with organizational functions. Strategic planning is seen as an orderly and continuous process. This process includes anticipatory knowledge-based decision making, organizing activities to implement decisions, and measuring results through systematic feedback. For the purpose of strategic planning, which is the main element in building organizational performance, providing comprehensive guidance to achieve the vision, mission and goals of the organization.